A study of serum zinc levels in children admitted with pneumonia in a tertiary care hospital in India - Naushad, Ashrin A; Naushad, Ashrin A; Kailas, Lalitha; Sivaraman, Sreekanth K (Indian Journal of Child Health, 2021)
Background: Worldwide, pneumonia is a leading cause of morbidity and mortality in children under 5 years of age; especially, in developing countries. Objectives: The objective of the study is to investigate whether zinc deficiency and other nutritional factors are related to pneumonia in children between 6 months and 5 years old. Methodology: In this casecontrol study, a valid written consent was obtained from mothers of enrolled children. The cases included 75 children fulfilling the World Health Organization criteria for pneumonia, between the age group of 6 months and 5 years. They were interrogated for potential nutritional risk factors as per a predesigned proforma followed by a measurement of serum zinc levels. In the control group, 75 children of the same age group who were siblings of admitted children were included along with other children of the same age group admitted for non-respiratory complaints. A detailed case history was obtained and physical examination was done according to a predesigned proforma to elicit various potential risk factors. A semi-auto analyzer was used to measure the serum zinc levels through colorimetric methods using 5-bromo-PAS. Results: Significant nutritional risk factors identified were low serum zinc level, malnutrition, and anemia. Conclusion: The present study has identified various nutritional risk factors for pneumonia which can be tackled through effective education of the community and appropriate initiatives.